(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Yurasbe NQ, Din NA, Palaniveloo K, Manikam S, Nagappan T. 2023. Phytochemical diversity and biological activities of Curcuma species from the East Coast of Peninsular Malaysia. Biodiversitas 24: 4243-4252. Zingiberaceae has been associated with traditional medicine for centuries. The genus Curcuma is traditionally famous and economically important for its therapeutic and nutritional values. Over 50 genera of 1600 species are recorded worldwide, with the highest concentration in the Malesian region, including Indonesia, Borneo, Thailand, Malaysia, Vietnam, Cambodia, Myanmar, and the Philippines. We investigated the methanolic crude extracts of Curcuma aeruginosa, Curcuma caesia, Curcuma longa, Curcuma xanthorrhiza, and Curcuma zedoaria from Terengganu for their phytochemicals, total phenolic content (TPC) using Folin-Ciocalteu colorimetric method, total flavonoid content (TFC) using aluminum chloride colorimetric method, antioxidant activity using the 2,2-diphenyl-1-picryl-hydrezyl (DPPH) radical scavenging activity and toxicity using brine shrimp lethality test (BSLT). Phytochemical screening revealed alkaloids, flavonoids, phenolics, saponins, tannins, triterpenoids, glycosides, lignins, and oils in all species investigated. Curcuma longa extract had the highest phenolic and flavonoid content with the value of 155.31±1.78 mg GAE/g and 151±8.35 mg quercetin/g, respectively as well as best antioxidative potential with IC50 value of 88.65±0.6 mg/mL, followed by C. zedoaria (98.61±5.23 mg/mL), C. aeruginosa (142.51±3.29 mg/mL), C. xanthorrhiza (150.01±0.63 mg/mL) and C. caesia (156.4±0.67 mg/mL). Curcuma caesia displays the lowest degree of toxicity compared to the other species, with the LC50 value of 11585 mg/mL) considered non-cytotoxic. Hence, the selected Curcuma species has potential therapeutic value to be developed into pharmaceutical due to its significant bioactive potentials and potent antioxidant capacity.